Role of Platelet-Rich Plasma in Articular Cartilage Injury and Disease - Mascarenhas, Randy; Saltzman, Bryan M.; Fortier, Lisa A.; Cole, Brian J. (The Journal of Knee Surgery, 2015)
Clinical and laboratory research aimed at biological approaches to cartilage repair are currently in high demand due to the poor regenerative capacity of articular cartilage in the setting of a diseased articular environment. Platelet-rich plasma (PRP) takes advantage of supraphysiological concentrations of platelets and their growth factors harbored in α-granules, which together attempt to return the diseased articular cartilage to a preinjury state. The local use of PRP directly at the site of cartilage injury is thought to stimulate a natural healing cascade and accelerate the formation of cartilage repair tissue. This article provides an overview of the basic science behind the use of PRP in the treatment of cartilage injury and disease. Both initial and current examples of the use of intra-articular PRP in clinical human studies are provided. These include the use of PRP either alone or as an augmentation device with various other procedures, including arthroscopic microfracture and cell-free resorbable polyglycolic acid-hyaluronan implantation. Finally, the authors describe some of the potential future roles of PRP in clinical settings based on recent literature. These include Achilles tendon rupture, chronic tendinosis, chronic rotator cuff tendinopathy or tearing, muscle injury, and meniscal repair.
Keywords: articular cartilage; osteoarthritis; platelet-rich plasma; PRP